A Rule Based Question Answering System in Malayalam Corpus Using Vibhakthi and POS Tag Analysis. (2016) - Archana, S.M.; Vahab, Naima; Thankappan, Rekha; Raseek, C.
Abstract: Malayalam is an agglutinative language. Only a few numbers of works have been done in question answering system for Malayalam. To denote a relation to the verb or any other name some morphophonemic modifications are added to the noun in Malayalam sentences. These modifications are performed using vibhakthi. For example: etc. Here we proposed a QA system which gives word level answers by comparing vibhakthi and POS tags of question words, words in the corpus given as answer set.